Unsung Hero of Gettysburg : The Story of Union General David McMurtrie Gregg - Longacre, Edward G., 1946- (Book collections on Project MUSE., 2021)
"Unsung Hero of Gettysburg: The Story of Union General David McMurtrie Gregg explores the honorable but neglected thirty-three-year old Commander of the Potomac Army David McMurtrie Gregg during Gettysburg, the pivotal battle of the Civil War"--